2014
DOI: 10.1016/j.ijgo.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Decentralizing postabortion care in Senegal with misoprostol for incomplete abortion

Abstract: The results provide further evidence that 400 μg of misoprostol is highly effective for first-line treatment of incomplete abortion. Furthermore, this regimen can be fully provided by nurse midwives, and can be easily and successfully introduced in community health settings where other methods of PAC may not previously have been available. Clinicaltrials.gov: NCT01939457.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
4
20
0
Order By: Relevance
“…The overall complete abortion rate in our study was similar to results in previous studies (range 94-99%). 8,10,29 Decentralisation of misoprostol use in post-abortion care has been successful in a similar setting, where ultrasound is not routinely used and physicians are scarce, 24 which is consistent with our fi ndings. In Uganda, most physicians work in the central urban region serving less than one third of the population.…”
Section: Discussionsupporting
confidence: 88%
“…The overall complete abortion rate in our study was similar to results in previous studies (range 94-99%). 8,10,29 Decentralisation of misoprostol use in post-abortion care has been successful in a similar setting, where ultrasound is not routinely used and physicians are scarce, 24 which is consistent with our fi ndings. In Uganda, most physicians work in the central urban region serving less than one third of the population.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike surgical PAC (manual or electric vacuum aspiration or dilation and curettage), misoprostol requires no surgical skills or equipment to administer making it feasible to scale up in resource scarce settings [34]. However, there is limited availability of misoprostol in facilities offering maternity services in Senegal [14] which may be due to lack of awareness of its reproductive health uses and limited supply of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Several brands of misoprostol exist on the market today, one of which, Misoclear®, is registered for gynaecological indications such as PPH and PAC. Recent research on misoprostol provision at the community level for PPH and PAC in Senegal has shown high levels of efficacy and acceptability [13, 14] and found it to be more cost effective for PPH prevention than oxytocin [15]. However, misoprostol remains underused [13, 14], and its availability in public and private health facilities is limited [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such revisions might include integrating MVA into the national medical supply system and into national training curricula for nurses and midwives. A recent study demonstrated the effectiveness of Misoprostol in treating incomplete abortion at community health posts in Senegal (Gaye et al 2014). This drug should also be available through the national medical supply system as a form of PAC treatment.…”
Section: Discussionmentioning
confidence: 99%